Phylogenetic analysis of pitcher plant Nepenthes spp. from South Sumatra Based on ITS rDNA sequence - Lestari, Weni; Jumari, Jumari (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2026)
Nepenthes spp. are carnivorous plants that have special leaf modifications with various shapes, sizes, and color patterns. Knowledge of Nepenthes spp. species in South Sumatra is still limited because there has been no comprehensive research. This study aims to identify and analyze the phylogenetics of Nepenthes spp. from South Sumatra based on Internal Transcribed Spacer (ITS) rDNA sequences. Sampling was carried out in the forests of Tekorejo Village, Air Itam Village and cultivation sites in Palembang, South Sumatra, Indonesia. Molecular identification was carried out by DNA isolation, qualitative and quantitative tests, amplification of the ITS rDNA region using primer pairs ITS1 and ITS4, identification of ITS rDNA sequences, and phylogenetic analysis using the NJ (Neighbor Joining) tree method in MEGA 6 software. The identification results showed that there are 9 variants of Nepenthes spp. included in the species N. mirabilis, N. gracilis, and N. sumatrana. The phylogenetic tree from molecular analysis shows a monophyletic line between N. mirabilis, N. gracilis, and N. sumatrana with a genetic closeness between N. mirabilis and N. gracilis of 0.009 while the relationship between N. mirabilis and N. sumatrana is relatively distant, with a genetic distance of 0.066. The results of this study provide new genetic baseline data that serve as an important source of information for taxonomic purposes and conservation efforts of Nepenthes spp. in South Sumatra for sustainable development and utilization of local plants.